New Vistas in microRNA Regulatory Interactome in Neuropathic Pain - Gada, Yash; Pandey, Amitkumar; Jadhav, Nikita; Ajgaonkar, Saiprasad; Mehta, Dilip; Nair, Sujit (Frontiers in Pharmacology, 2022)
Neuropathic pain is a chronic pain condition seen in patients with diabetic neuropathy, cancer chemotherapy-induced neuropathy, idiopathic neuropathy as well as other diseases affecting the nervous system. Only a small percentage of people with neuropathic pain benefit from current medications. The complexity of the disease, poor identification/lack of diagnostic and prognostic markers limit current strategies for the management of neuropathic pain. Multiple genes and pathways involved in human diseases can be regulated by microRNA (miRNA) which are small non-coding RNA. Several miRNAs are found to be dysregulated in neuropathic pain. These miRNAs regulate expression of various genes associated with neuroinflammation and pain, thus, regulating neuropathic pain. Some of these key players include adenylate cyclase (Ac9), toll-like receptor 8 (Tlr8), suppressor of cytokine signaling 3 (Socs3), signal transducer and activator of transcription 3 (Stat3) and RAS p21 protein activator 1 (Rasa1). With advancements in high-throughput technology and better computational power available for research in present-day pharmacology, biomarker discovery has entered a very exciting phase. We dissect the architecture of miRNA biological networks encompassing both human and rodent microRNAs involved in the development of neuropathic pain. We delineate various microRNAs, and their targets, that may likely serve as potential biomarkers for diagnosis, prognosis, and therapeutic intervention in neuropathic pain. miRNAs mediate their effects in neuropathic pain by signal transduction through IRAK/TRAF6, TLR4/NF-κB, TXIP/NLRP3 inflammasome, MAP Kinase, TGFβ and TLR5 signaling pathways. Taken together, the elucidation of the landscape of signature miRNA regulatory networks in neuropathic pain will facilitate the discovery of novel miRNA/target biomarkers for more effective management of neuropathic pain.